Freshwater fishes of northern Australia - Pusey, Bradley J.; Burrows, Damien W.; Kennard, Mark J.; Perna, Colton N.; Unmack, Peter J.; Allsop, Quentin; Hammer, Michael P. (Zootaxa, 2017)
Northern Australia is biologically diverse and of national and global conservation signicance. Its ancient landscape contains the world’s largest area of savannah ecosystem in good ecological condition and its rivers are largely free-flowing. Agriculture, previously confined largely to open range-land grazing, is set to expand in extent and to focus much more on irrigated cropping and horticulture. Demands on the water resources of the region are thus, inevitably increasing. Reliable information is required to guide and inform development and help plan for a sustainable future for the region which includes healthy rivers that contain diverse fish assemblages. Based on a range of information sources, including the outcomes of recent and extensive new field surveys, this study maps the distribution of the 111 freshwater fishes (excluding elasmobranches) and 42 estuarine vagrants recorded from freshwater habitats of the region. We classify the habitat use and migratory biology of each species. This study provides a comprehensive assessment of the diversity and distribution of fishes of the region within a standardised nomenclatural framework. In addition, we summarise the outcomes of recent phylogeographic and phylogenetic research using molecular technologies to identify where issues of taxonomy may need further scrutiny. The study provides an informed basis for further research on the spatial arrangement of biodiversity and its relationship to environmental factors (e.g. hydrology), conservation planning and phylogentic variation within individual taxa.